Geospatial-temporal coupling of urbanisation and water resources: landscape dynamics in Nanchang, China - Wang, Juan; Luo, Zhenzhen; Yu, Benfeng; Yang, Qingpei; Li, Jianfeng; Wu, Chunsheng; Khai, Ern Lee (Penerbit Universiti Kebangsaan Malaysia, 2026)
Rapid urbanisation necessitates an understanding of the coupling coordination between urban expansion and water resources to inform sustainable development strategies. However, research on this relationship remains limited in less economically developed regions. This study addresses the gap by examining Nanchang City, Jiangxi Province, China, using land use and socio-economic data (2000-2020) to analyse geospatial-temporal changes in land use and landscape patterns of construction land and water bodies. A coupling coordination model is applied to assess the relationship between urbanisation and water resources. Findings indicate that cultivated land, water bodies and forest land were major sources of new construction land. The expansion rate and intensity of construction land initially declined before increasing, peaking in 2000-2005. The fractal dimension exhibited a steady rise, while compactness remained relatively stable. Water body area, landscape shape index and edge density generally declined. Landscape fragmentation, separation and cohesion indices fluctuated between 2000 and 2015 but changed significantly in 2015-2020. Spatial overlap between the centroids of construction land and water bodies varied (1.8904-2.9465 km), following a positive-negative-positive cyclical pattern. The coupling coordination degree between urbanisation and water resources improved, progressing through stages from ‘Moderately Unbalanced’ to ‘Highly Balanced’. To foster an urban-water symbiotic pattern, ecological corridors within the water system should be established and construction land boundaries delineated with caution. These findings offer valuable insights for urban planning and water resource management in Nanchang City and other rapidly developing regions.